Analisis Penggunaan Dana Biaya Operasional Sekolah Reguler Terhadap Hasil Belajar Siswa Jenjang SMP - M. Ridwan Tikollah; Sitti Hajerah Hasyim; Nuraisyiah Nuraisyiah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2022)
Abtract: This study aimed: (1) to describe the use of Regular School Operational Costs (BOS) funds in Junior High School (SMP) level, and (2) to describe the effect of the use of Regular BOS funds for the quality of learning expenditure on the learning outcomes of SMP level students. This research was an associative-causal research which explained the use of Regular BOS for quality of learning expenditure and its effect on student learning outcomes. The research population was all SMP in Maros Regency, while the sample was taken using purposive sampling technique. Data collection was done by documentation technique. Data analysis for hypothesis testing was carried out with simple linear regression analysis and t-test. The results showed: 1) The use of Regular BOS funds in SMP level was focused on the quality of learning expenditure; 2) The use of Regular BOS funds for quality of learning expenditure had an effect on student learning outcomes of SMP level students in Maros Regency. Keyword: the use of Regular BOS, learning outcomes